Medicated chewing gums - A novel targeted drug delivery - Nimesh Jain; Manisha Jadhav; Rajeshwari G Annigeri; Pratik R Pipaliya (Wolters Kluwer Medknow Publications, 2019)
The potential of medicated chewing gum (MCG) for buccal delivery, fast onset of action makes it an attractive delivery form. It is considered as vehicle or a drug delivery system to administer active principles that can improve health and nutrition. Chewable tablets and chewing gum (CG) permit more rapid therapeutic action compared to per-oral dosage forms. Chewable tablets and CGs have been very well received by the parents for use in children with full dentition. MCG is feasible in local treatment of diseases of oral cavity as well as treatment of systemic conditions. This newer drug delivery system could be a boon in treating oral diseases as it is a non-invasive mode of drug delivery.